Recent advances in the dissection of drought-stress regulatory networks and strategies for development of drought-tolerant transgenic rice plants - Todaka, Daisuke; Shinozaki, Kazuo; Yamaguchi-Shinozaki, Kazuko (Frontiers in Plant Science, 2015)
Advances have been made in the development of drought-tolerant transgenic plants, including cereals. Rice, one of the most important cereals, is considered to be a critical target for improving drought tolerance, as present-day rice cultivation requires large quantities of water and as drought-tolerant rice plants should be able to grow in small amounts of water. Numerous transgenic rice plants showing enhanced drought tolerance have been developed to date. Such genetically engineered plants have generally been developed using genes encoding proteins that control drought regulatory networks. These proteins include transcription factors, protein kinases, receptor-like kinases, enzymes related to osmoprotectant or plant hormone synthesis, and other regulatory or functional proteins. Of the drought-tolerant transgenic rice plants described in this review, approximately one-third show decreased plant height under non-stressed conditions or in response to abscisic acid treatment. In cereal crops, plant height is a very important agronomic trait directly affecting yield, although the improvement of lodging resistance should also be taken into consideration. Understanding the regulatory mechanisms of plant growth reduction under drought stress conditions holds promise for developing transgenic plants that produce high yields under drought stress conditions. Plant growth rates are reduced more rapidly than photosynthetic activity under drought conditions, implying that plants actively reduce growth in response to drought stress. In this review, we summarize studies on molecular regulatory networks involved in response to drought stress. In a separate section, we highlight progress in the development of transgenic drought-tolerant rice plants, with special attention paid to field trial investigations.